Roundtable: The Digital Humanities: A Common Ground for Experimentation - Carlos Ceia; Fátima Vieira; Federico Boschetti; Nils Geißler; Joana Pinela; Luciano Moreira; Raquel Correia de Souza; Joel Ramos Faustino (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Transcript of Roundtable "The Digital Humanities: A Common Ground for Experimentation"